Stress Responses from the Endoplasmic Reticulum in Cancer - Kato, Hironori; Nishitoh, Hideki (Frontiers in Oncology, 2015)
The endoplasmic reticulum (ER) is a dynamic organelle that is essential for multiple cellular functions. During cellular stress conditions, including nutrient deprivation and dysregulation of protein synthesis, unfolded/misfolded proteins accumulate in the ER lumen, resulting in activation of the unfolded protein response (UPR). The UPR also contributes to the regulation of various intracellular signalling pathways such as calcium signalling and lipid signalling. More recently, the mitochondria-associated ER membrane (MAM), which is a site of close contact between the ER and mitochondria, has been shown to function as a platform for various intracellular stress responses including apoptotic signalling, inflammatory signalling, the autophagic response, and the UPR. Interestingly, in cancer, these signalling pathways from the ER are often dysregulated, contributing to cancer cell metabolism. Thus, the signalling pathway from the ER may be a novel therapeutic target for various cancers. In this review, we discuss recent research on the roles of stress responses from the ER, including the MAM.